2023
DOI: 10.1021/acscatal.3c03063
|View full text |Cite
|
Sign up to set email alerts
|

Weak Interaction between Nickel Thiolate and g-C3N4 Improving Electron–Hole Separation for Photocatalysis

Fan Tian,
Xiaofei Huang,
Wangxuan Li
et al.

Abstract: Developing strategies to accelerate the electron−hole pair separation and understanding the mechanism are important for improving the activity of photocatalysts. Herein, constructing a weak interaction between nickel thiolate cluster (i.e., Ni 12 (SPhCH 3 ) 24 ) and graphitic carbon nitride (g-C 3 N 4 ) is revealed as an effective strategy to regulate electron−hole pair separation. The π−π interaction between the triazine rings in g-C 3 N 4 and the phenyl rings in Ni 12 (SPhCH 3 ) 24 offers a primary pathway f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…For Ag 33 -p-BMTC, complete conversion of 4-nitrophenol to 4-aminophenol could be reached in less than 20 min, while 60 and 240 min were needed for Ag 33 -p-BMTM and Ag 33 –PET, respectively (Figure d). Loading these nanoclusters on g-C 3 N 4 (Figure S4) or using the crystal powder directly (Figure S5) as the catalysts also showed the same tendency that the catalytic activity followed Ag 33 -p-BMTC > Ag 33 -p-BMTM > Ag 33 –PET. The blank test with NaBH 4 replaced by NaOH showed that no distinct conversion of 4-nitrophenol was observed over Ag 33 -p-BMTC (Figure S6), indicating that the reaction between Ag 33 nanocluster and 4-nitrophenol was ignorable.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…For Ag 33 -p-BMTC, complete conversion of 4-nitrophenol to 4-aminophenol could be reached in less than 20 min, while 60 and 240 min were needed for Ag 33 -p-BMTM and Ag 33 –PET, respectively (Figure d). Loading these nanoclusters on g-C 3 N 4 (Figure S4) or using the crystal powder directly (Figure S5) as the catalysts also showed the same tendency that the catalytic activity followed Ag 33 -p-BMTC > Ag 33 -p-BMTM > Ag 33 –PET. The blank test with NaBH 4 replaced by NaOH showed that no distinct conversion of 4-nitrophenol was observed over Ag 33 -p-BMTC (Figure S6), indicating that the reaction between Ag 33 nanocluster and 4-nitrophenol was ignorable.…”
Section: Resultsmentioning
confidence: 71%
“…However, understanding the precise correlation between the surface states and catalytic process still remains challenging owing to the polydispersity of these catalysts with each particle having different surface structures and not being able to be resolved atomically with the current characterization techniques. , Ligand-protected metallic nanoclusters, as a new kind of nanomaterials, not only possess atomically precise characteristics but also exhibits similar structure and composition of the corresponding nanocatalysts, which can be as ideal platforms to investigate the precise catalytic mechanism of typical reactions. Furthermore, the ultrasmall size of the nanoclusters endows its properties and behaviors differing from the individual atoms or bulk metals, which also offers the chances to study the effects of single sites regulation in fundamental material science and applications . So far, certain amounts of ligand-protected nanoclusters have been successfully developed as efficient catalysts or cocatalysts in thermocatalysis, photocatalysis, or electrocatalysis. Some of them exhibit robust activities even comparable to those of the corresponding colloid nanoparticles. These reports indicate that employing nanoclusters as heterogeneous catalysts is valuable not only in theoretical research but also in application prospect.…”
Section: Introductionmentioning
confidence: 99%
“…employed sulfur-substituted nickel nanoclusters to modify g-C 3 N 4 , leading to a 230-fold increase in the efficiency of photocatalytic hydrogen evolution. This discovery highlights the expedited separation of electron–hole pairs, consequently amplifying the effectiveness of photocatalysis . Recently MoS 2 stands out for its distinctive photonic, electronic, and physicochemical attributes, capturing the keen interest of researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Graphitic carbon nitride (g-C 3 N 4 ), as a hotspot semiconductor material, has been extensively applied in the photocatalysis field due to its excellent catalytic performance, non-toxicity, low cost, and fantastic chemical and thermal stability. [1][2][3][4][5][6][7][8][9][10] In addition, g-C 3 N 4 also exhibits fascinating optical properties, broadband emission and tunable photoluminescence (PL) spectra, making it highly promising for luminescence applications. [11][12][13][14][15] To pursue excellent optical performance, numerous strategies involving atomic doping [16][17][18][19] and molecular modification 14,[20][21][22][23][24] have been employed to improve g-C 3 N 4 materials.…”
Section: Introductionmentioning
confidence: 99%